Combined radius addition osteotomy and ulnar shortening to correct extra-articular distal radius fracture malunion with severe radial deviation and ulnar plus: Running title: Distal radius malunion addition osteotomy and ulna procedure - Marcuzzi, Augusto; Lana, Debora; Laselva, Onofrio; Pogliacomi, Francesco; Leigheb, Massimiliano; Adani, Roberto (Acta Biomedica Atenei Parmensis, 2019)
Malunion can occur in 11 to 28% of Distal Radius Fractures and can result in radius shortening and ulnar plus with wrist deviation, pain and disability. We aimed to report particular cases of extra-articular distal radius fracture malunion with severe radial deviation and ulnar plus treated by corrective osteotomy of distal radius with bone graft associated to ulnar procedure. One of these patients was firstly operated with ulna subtraction osteotomy synthesized with plate and in a second stage with distal radius corrective addition osteotomy with homologous bone graft, plate and external fixator. Two other cases were treated in a single-step by radius addition osteotomy and caput ulnae Darrach resection. These three patients were followed-up from 2 to 12 years, successfully observing the maintenance of anatomical correction and recovery of ROM and strength with good pain relief and return to daily activities. After Darrach procedure external-fixation wasn’t needed and pronation-supination was better. Darrach procedure can solve ulna plus and improve ROM in pronation-supination with a quicker healing, avoiding the risk of ulnar non-union. Darrach’s procedure associated to addition corrective osteotomy of distal radius can be a valid treatment for distal radius severe malunion, in patients with low-moderate functional demand. In conclusion, the surgeon should choose the right corrective treatment after the complete evaluation of the patient and his functional needs.